LYCOPENE: MOST POTENT ANTIOXIDANT WITH ENDLESS BENEFITS - NUPUR SINHA; DEEPTI DUA (International Journal of Pharma and Bio Sciences, 2015)
Lycopene is the most-potent antioxidant among various common carotenoids. Carotenoids are colored compounds found in the photosynthetic pigments in fruits and vegetables which provide them their bright colors and benefit human health by playing an important role in cell function. Red fruits and vegetables, including tomatoes, watermelons, pink grapefruits, apricots and pink guavas contain lycopene. Processed tomato products such as juice, ketchup, paste, sauce and soup all are good dietary sources of lycopene. It is a lipophilic, 40-carbon atom and highly unsaturated, straight open chain hydrocarbon containing 11 conjugated and 2 non-conjugated double bonds. Many conjugated double bonds of lycopene make it a potentially powerful antioxidant, a characteristic believed to be responsible for its beneficial effects. It is a potent neuroprotective, anti-proliferative, anticancer, anti-inflammatory, cognition enhancer and hypo-cholesterolemic agent. Lycopene’s role has also been found to be positive in the management of cataract, malaria, immune modulation, Alzheimer’s disease, perclampsia, infertility, aging, osteoporosis, and even male infertility.